Virtual bandwith SAR (VB-SAR) for centimeter-scale vertical profiling through a soil at C-band from space - Morrison, Keith; Edwards-Smith, Alexander; Zwieback, Simon; Hajnsek, Irena (IEEE, 2019)
The first experimental demonstration of the Virtual Bandwidth SAR (VB-SAR) scheme is provided. VB-SAR is a new technique that promises subsurface imaging of soils at ultra-high, centimeter-scale resolution at large stand-off distances applicable to aircraft and spacecraft. This paper reports on how a stack of C-band images were used to retrieve high resolution vertical profiles of the backscattering through a soil in the laboratory. The VB-SAR scheme captures the phase behavior of a soil across a stack of DInSAR images as the soil dries. The real frequency of the interrogating radar behaves as a higher, virtual frequency within the soil by virtue of its higher-than-air dielectric. As the dielectric changes with time, the DInSAR stack captures a virtual bandwidth. Using this scheme, it was possible to produce a vertical slice of the backscatter through a soil at 10cm resolution, much improved on the formal 1m resolution offered by the real 150MHz bandwidth.
Keywords: virtual bandwith SAR scheme; virtual band-with synthetic aperture radar; soil centimeter-scale vertical profiling; space C-band images; soil subsurface imaging; high resolution soil backscattering vertical profiles; DInSAR images